Utilization of Melon Skin Waste (Cucumis Melo L.) in Syrup Preparations as an Immunostimulant to Prevent Covid-19 - Andi Nur Ilmi Adriana; Firmansyah Firmansyah; Muhammad Taufiq Duppa (Institute of Computer Science (IOCS), 2022)
Today, the world is being shaken by a great pandemic called Covid-19 (Corona Virus Disease). The increase from day to day in the number of patients infected with the Covid-19 virus is already difficult to control. A clear and straightforward plan is needed from the government to tackle this problem. Efforts to increase the body's resistance so as not to be easily attacked by viruses are also important. The immune system can be increased by consuming nutritious foods and sources of bioactive components that have immunostimulant activity. Natural ingredients that can be used to prevent Covid-19 are melons. The utilization of melon peel waste is currently still not optimal, this melon skin actually contains a lot of substances that are useful for health. Melon peel is rich in nutrients such as carbohydrates (69.77%) and ash (3.67%). They contain a large amount of total dietary fiber (41.69%) and antioxidants as polyphenols and flavonoids (332mg/100g extract and 95.46mg/100g extract, respectively). Identification and quantification of melon peel phenolic compounds. showed that hydroxybenzoic acid and flavones constituted their main phenolic class. 3-Hydroxybenzoic acid was the main phenolic compound in melon peel at 33.45mg/100g, followed by apigenin-7-glycoside (29.34mg/100g. This research was conducted by formulating melon peel extract in three concentration variations, namely FI (extract 10) %) FII (15% extract) and FIII (20% extract). The syrup preparation of melon peel extract obtained was then subjected to accelerated stability test. The phagocytosis test was carried out by calculating the phagocytic activity of macrophage cells. Data analysis using the Graphad Prism® application. The results obtained the watermelon rind extract syrup formula is stable after storage and can act as an immunostimulant.